Chitosan-based nanocapsules of core-shell architecture - Szafraniec, J.; Odrobińska, J.; Lachowicz, D.; Kania, G.; Zapotoczny, S. (Polimery, 2021)
N-dodecyl derivative of cationically modified chitosan was used to prepare core-shell nanocapsules templated on liquid cores. Surfactant-free method based on ultrasound-assisted direct emulsification of aqueous solution of polysaccharide with oleic acid was applied. Formation of spherical capsules was confirmed by scanning and transmission electron microscopies. Dynamic light scattering measurements were used to determine physicochemical parameters of the obtained particles as well as to follow the process of multilayer shell formation. Confocal microscopy was applied to examine the ability of encapsulation of hydrophobic compounds inside the cores of the nanocapsules. Performed studies confirmed that hydrophobically modified cationic chitosan provides long-term stabilization of oil-in-water emulsion for biomedical applications as no toxic effect was observed in acute oral toxicity studies.